EFEKTIVITAS PELAKSANAAN TUGAS POS KERJA TANJUNG BERLIAN KANTOR UNIT PENYELENGGARA PELABUHAN TANJUNG BERLIAN KUNDUR UTARA KABUPATEN KARIMUN - Hendra Dinata; Harapan Tua (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Kundur Islands is one of uplift in the Riau Islands province, Kundur Island is one of a small town with shipping activity. No wonder if in Kundur Island harbors many of the people there. To manage all the activities in all the ports of the people in the region Kundur islands, then Pos formed under the auspices of the Working Syahbandar Implementation Unit Port (KUPP) Kundur. According to Law No. 17 of 2008 on the cruise, carry out the functions of the port safety and security of shipping which includes implementation, monitoring and enforcement in the field of transport in the waters, ports, and maritime environmental protection at the port. However, based on the authors observations Tanjung Berlian, still a lot of the discrepancy between theory and practice that occur in the field. Examples are as follows: lack of a clear process of issuance of Letter of Approval Sailing (SPB) for shipping agents in ports, Less neat and completeness of documents manning ships that operate in the Post Employment Cape Diamond, Less conduct surveillance and Sailing Bandar tongue in their respective work stations.Based on the above phenomena, the formulation of the problem in this research is: How Workplace Effectiveness of Post Office Task Execution Unit Operator Tanjung Diamond District of North Kundur, Karimun and Factors Affecting Implementation Task Effectiveness of Post Employment Cape Diamond District of North Kundur Karimun.The purpose of this study was to examine the effectiveness of the Post Implementation Task Work Cape Diamond, North Kundur, Karimun Regency and Knowing the factors that influence the effectiveness of post work assignments Cape Diamond. Theory (approach) is used as an analytical tool in this study is about the effectiveness of the proposed theory by Sumaryadi (2005: 105) effectiveness is how well the work take place, where a person menghaliskan sjauh output as expected. While the research methods used in this study is descriptive qualitative research that is intended to provide an overview of systematic explanation of the observed phenomenon.Based on the results of field research on the effectiveness of the writer peaksanaan task Cape Diamond workstations running the Less Well, it can be seen from inspection of the complete document indent indicator ship and crew as well as the issuance of Letter of Approval process indicators that are sailing in the unfavorable category. So far the implementation of the tasks performed areJom FISIP Volume 1 No. 2 –Oktober 2014 2administrative in nature but only in the form directly in the field pelaksnaan task is still very rare.Keywords: Efectiviness, Implementation, Principal Duties and Functions.